Synthesis of polycaprolactone-hydroxyapatite (PCL-HA) biodegradable nanofibres via an electrospinning technique for tissue engineering scaffolds - Muhammad Zikri Aiman Zulkifli,; Shazwani Amenina Sharbani,; Darman Nordin,; Norazuwana Shaari,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The interest in biodegradable polymer nanofibres with tissue cell regeneration potential has increased in recent years. However, there are issues in the development of scaffolding to provide a favourable environment for cell proliferation and attachment. Such issues can be overcome by the addition of hydroxyapatite (HA), which is widely used in biomaterial applications. Biodegradable nanofibres of polycaprolactone (PCL) and hydroxyapatite (HA) have been produced by electrospinning. In this study, PCL was mixed with HA to synthesise nanofibres by single nozzle electrospinning. Furthermore, PCL-HA nanofibres were mixed with fibronectin to investigate the effect of adhesion of fibronectin to the surface of the PCL-HA nanofibres. The structure and morphology of nanofibres were determined by scanning electron microscopy (SEM), the chemical properties of nanofibres were analysed by Fourier transform infrared (FTIR), and the diameter and adhesive force of nanofibers and fibronectin were determined by an atomic force microscope (AFM). The SEM examination revealed the formation of cylindrical and smooth nanofibres with dense fibre networks when 10% HA was used, as HA can generate fibre. FTIR analysis indicated the presence of PCL and HA inside the nanofibres produced by electrospinning. The AFM examination showed that the PCL-HA nanofibres with 100 μg/ml of fibronectin gives the highest adhesion force which is important for the scaffold to resist the force from the external environment. This outcome resulted indicates that the PCL-HA nanofibers with fibronectin are promising for tissue engineering scaffold application. Hence, further investigations are needed to ensure the compatibility of living cells to survive and grow on the PCL-HA nanofibrous mats.